Using Social Media to Support the Special Autonomous Region of Papua's Continuity Program - Arissy Jorgi Sutan; Titin Purwaningsih (Journal of Governance, 2022)
Social media has become part of society; in 2021, citizen Indonesia trends issue of continuity program particular autonomous region of Papua. This research examines what kind of social media supports Papua's continuity, mainly autonomous region programs. This study employed a qualitative method and analyzes data using Qualitative Data Analysis Software (Q-DAS); the toll is Nvivo 12Plus and delivers the value and result using Descriptive way. This research founds that: First, social media Dominated three terms on social media. Second, social media hashtags relation also appears and exits. Third, social media Narratives refer to support the program of a special autonomous region in Papua. Forth, social media dominance with Individual and Ngo. This study has significant drawbacks. This study focused on the use of social media to help Papua's special autonomous area. Some recommendations to the next research is to assist the Papua's special autonomous region program.